Mitochondrial remodeling in human skin fibroblasts from sporadic male Parkinson's disease patients uncovers metabolic and mitochondrial bioenergetic defects - Deus, Cláudia M. (2020)
Parkinson's Disease (PD) is characterized by dopaminergic neurodegeneration in the substantia nigra. The exact mechanism by which dopaminergic neurodegeneration occurs is still unknown; however, mitochondrial dysfunction has long been implicated in PD pathogenesis. To investigate the sub-cellular events that lead to disease progression and to develop personalized interventions, non-neuronal cells which are collected in a minimally invasive manner can be key to test interventions aimed at improving mitochondrial function. We used human skin fibroblasts from sporadic PD (sPD) patients as a cell proxy to detect metabolic and mitochondrial alterations which would also exist in a non-neuronal cell type. In this model, we used a glucose-free/galactose- glutamine- and pyruvate-containing cell culture medium, which forces cells to be more dependent on oxidative phosphorylation (OXPHOS) for energy production, in order to reveal hidden metabolic and mitochondrial alterations present in fibroblasts from sPD patients. We demonstrated that fibroblasts from sPD patients show hyperpolarized and elongated mitochondrial networks and higher mitochondrial ROS concentration, as well as decreased ATP levels and glycolysis-related ECAR. Our results also showed that abnormalities of fibroblasts from sPD patients became more evident when stimulating OXPHOS. Under these culture conditions, fibroblasts from sPD cells presented decreased basal respiration, ATP-linked OCR and maximal respiration, and increased mitochondria-targeting phosphorylation of DRP1 when compared to control cells. Our work validates the relevance of using fibroblasts from sPD patients to study cellular and molecular changes that are characteristic of dopaminergic neurodegeneration of PD, and shows that forcing mitochondrial OXPHOS uncovers metabolic defects that were otherwise hidden.